Ekonomi Sirkular dalam Pengelolaan Persampahan Berkelanjutan: Tinjauan Literatur Sistematis tentang Tata Kelola Lingkungan dan Partisipasi Masyarakat - Haerul Anwar; Nurhayati; Syaharuddin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Background: The increasing global waste volume reaching 2.01 billion tons per year demands a paradigm transformation in waste management from a linear model toward a circular economy approach. Purpose: This study aims to analyze global trends in the application of circular economy in waste management, identify the roles of environmental governance and community participation, and formulate an evidence-based implementation model for West Lombok Regency. Method: A Systematic Literature Review (SLR) was conducted on 47 selected articles from Scopus, ScienceDirect, Google Scholar, and DOAJ databases (2016-2025) using the PRISMA protocol. Thematic analysis and narrative synthesis were employed. Findings: Three main themes were identified: (1) circular economy research trends show significant growth since 2019, focusing on waste valorization and zero waste strategies; (2) the effectiveness of environmental governance and community participation proved to increase waste management success by up to 68%; (3) a sustainable waste management model for West Lombok requires the integration of local policies, institutional capacity, and active community engagement. Conclusion: Circular economy offers a robust conceptual framework for waste management transformation, yet its success heavily depends on policy support and community participation. Implication: The findings provide strategic recommendations for the West Lombok local government in formulating inclusive and sustainable waste management policies based on circular economy principles.